Vaccine Impact on Long-term Trends in Invasive Bacterial Disease in New Zealand Children. Issue 10 (October 2018) - Walls, Tony; Cho, Vicki; Martin, Natalie; Williman, Jonathan; Brunton, Cheryl
Abstract : Background: Vaccines against Haemophilus influenzae type B (Hib), Neisseria meningitidis and Streptococcus pneumoniae have been serially introduced into the New Zealand national immunization schedule since the 1990s. This study aimed to describe long-term trends in the rates of these invasive bacterial infections in children from New Zealand and compare these to recent UK data. Methods: This population-based observational study used 2 national datasets that collect data about hospital discharges (National Minimum Dataset) and notifiable diseases (Epurv). Annual age-specific and age-standardized hospital admission rates and notification rates were analyzed for all children <15 years of age. Results: Hospital admissions for Hib reduced by 79% during the 2 years after the introduction of the Hib vaccine (5.94–1.24/100, 000). Meningococcal disease notifications fell by 75% over 8 years after the introduction of MeNZB vaccine (26.15–2.48/100, 000) and have continued to decline. Meningococcal disease rates were lower than in the United Kingdom despite the absence of an ongoing meningococcal vaccination program in New Zealand (8.16 compared with 10.37/100, 000 for 2007–2011). There rates of notifications and hospital admissions for pneumococcal disease were discordant, but both reduced substantially after the introduction of pneumococcal conjugate vaccines. Maori children had the highest rates of disease and the greatest reduction in rates after the introduction of both meningococcal and pneumococcal vaccines. Conclusions: Vaccines have had a substantial impact on the rates of invasive bacterial disease in children from New Zealand because of Hib, pneumococcus and meningococcus. Reductions in rates of disease have been greatest in Maori children, improving longstanding disparities in disease burden. Abstract : Supplemental Digital Content is available in the text.